Rosiglitazone Add-On in Treatment of Depressed Patients with Insulin Resistance: a Pilot Study - Natalie L. Rasgon; Heather A. Kenna; Katherine E. Williams; Bevin Powers; Tonita Wroolie; Alan F. Schatzberg (The Scientific World Journal)
A number of cross-sectional studies have suggested an association between insulin resistance (IR) and affective disorders. However, limited data exist on potential changes in IR in a prospective treatment of depression. The present pilot study tested the hypothesis that improvement of IR with the addition of an insulin-sensitizing agent would improve mood in nondiabetic patients with unipolar or bipolar depression, who had surrogate blood markers suggestive of IR. Surrogate IR-criteria blood markers were fasting plasma glucose >100 mg/dl or triglyceride (TG) to high density lipoprotein (HDL) ratio >3.0. Open-label rosiglitazone, titrated to a dose of 8 mg/day, was administered for 12 weeks to 12 patients with depressive disorder receiving treatment as usual (TAU). Eight patients who completed the 12-week study exhibited significant declines in both depression severity by the Hamilton Depression Rating Scale and the Clinical Global Impression scale, with moderate effect sizes noted. Modest improvement in Matsuda Index scores was also noted at 12 weeks, yet declines in depression severity scores were not associated with improvements in the endocrine markers (Matsuda Index, TG/HDL ratio, and body mass index). These results suggest the potential novel use for an insulin-sensitizing agent in the treatment of depressive disorders. Larger placebo-controlled studies are warranted.